Strengthening Affective Commitment Among Indonesian Lecturers: The Role of Organizational Support and Job Satisfaction - Lamin, Lamin; Hendriani, Susi; Machasin, Machasin; Efni, Yulia (Journal of Ecohumanism, 2024)
This study explores key factors influencing lecturers' affective commitment in Indonesian higher education. Utilizing a purposive sampling approach, data were collected from 288 private university lecturers in Riau Province and analyzed using Structural Equation Modeling (SEM) with Smart Partial Least Square (Smart PLS). Findings reveal that both organizational support and job satisfaction significantly and positively impact affective commitment, with the latter acting as a partial mediator. A novel aspect of this study is the formative measurement of job satisfaction indicators, providing a nuanced understanding of lecturers' experiences. The study underscores the need for targeted organizational strategies to foster commitment and satisfaction among educators.